MODERNISASI PENDIDIKAN ISLAM DALAM PERSPEKTIF AZYUMARDI AZRA - Aisah, Iis; Husni, H.; Darisman, Dede (Jurnal Penelitian Pendidikan Islam, 2015)
This research seeks to explore and analyze the concept of modernization of Islamic education according to Azyumardi Azra. The results of this study conclude that: 1) The concept of Islamic education concerns three important things, namely: a) the purpose of education, both general goals which are the purpose of human life, as well as special objectives that are praxis; b) Islamic education curriculum in addition to being oriented towards fostering and developing religious values ​​in students, must now also give special emphasis to the mastery of science and technology; c) democratization of Islamic education aims at the end of the formation of a democratic, clean, moral, and moral Indonesian society and clinging to the value of civilization; 2) Modernization of Islamic education according to Azyumardi Azra relating to: (a) Input from the community into the education system, including ideological-normative; Political mobilization; Economic mobilization; Social mobilization; Culture mobilization; (b) Output for the community. includes changes in the value system; Political output; Economic output; Social output; and cultural output; 3) The relevance of Azra's thinking about the modernization of Islamic education with national education that Islamic religious education is a compulsory curriculum that must be presented in learning.